2021
DOI: 10.1039/d1gc00724f
|View full text |Cite
|
Sign up to set email alerts
|

Biobased aliphatic polyesters from a spirocyclic dicarboxylate monomer derived from levulinic acid

Abstract: Levulinic acid derived from lignocellulose is an important biobased building block chemical. Here, we report on the synthesis and polymerization of a rigid spirocyclic diester monomer to produce polyesters and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 67 publications
(69 reference statements)
0
27
0
Order By: Relevance
“…The catalytic conversion of levulinic acid into 2-hydroxy-2-methylsuccinic acid (citramalic acid) was also reported [ 165 ], which is a high-value chemical that can replace succinic acid in polybutylene succinate, enhancing its properties. The synthesis of a cyclic diester via the ketalization of levulinic acid with pentaerythritol was described ( Figure 9 a), and the obtained monomer was polymerized by transesterification with 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, and 1,4-cyclohexanedimethanol, yielding fully amorphous polyesters with glass transition temperatures ranging from 12 to 49 °C and thermal stability up to 300 °C [ 166 ]. An analogous approach took advantage of the aromatic character of vanillin to synthesize the allyl ether monomer 3,9-bis(4-(allyloxy)-3-methoxyphenyl)-2,4,8,10-tetraoxaspiro [5.5]undecane ( Figure 9 b), which was mixed with thiols with different functionalities and polymerized through thiol-ene click photopolymerization to form the corresponding networks with tunable properties [ 167 ].…”
Section: Broadening the Horizon: Bio-based Routes For Original Polymersmentioning
confidence: 99%
“…The catalytic conversion of levulinic acid into 2-hydroxy-2-methylsuccinic acid (citramalic acid) was also reported [ 165 ], which is a high-value chemical that can replace succinic acid in polybutylene succinate, enhancing its properties. The synthesis of a cyclic diester via the ketalization of levulinic acid with pentaerythritol was described ( Figure 9 a), and the obtained monomer was polymerized by transesterification with 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, and 1,4-cyclohexanedimethanol, yielding fully amorphous polyesters with glass transition temperatures ranging from 12 to 49 °C and thermal stability up to 300 °C [ 166 ]. An analogous approach took advantage of the aromatic character of vanillin to synthesize the allyl ether monomer 3,9-bis(4-(allyloxy)-3-methoxyphenyl)-2,4,8,10-tetraoxaspiro [5.5]undecane ( Figure 9 b), which was mixed with thiols with different functionalities and polymerized through thiol-ene click photopolymerization to form the corresponding networks with tunable properties [ 167 ].…”
Section: Broadening the Horizon: Bio-based Routes For Original Polymersmentioning
confidence: 99%
“…The thermal stability of the polyesters was evaluated by TGA, as shown in Figure and Table . All the synthesized polyesters showed two thermal decomposition maxima ( T d ) between ∼278 and 460 °C . The lower temperature maximum is likely connected to the decomposition of imine bonds.…”
Section: Resultsmentioning
confidence: 97%
“…All the synthesized polyesters showed two thermal decomposition maxima (T d ) between ∼278 and 460 °C. 77 The lower temperature maximum is likely connected to the decomposition of imine bonds. This is supported by this maximum being the dominant decomposition step for the monomers, while the higher temperature maximum was the main decomposition step for the polymers, with the exception of SBP5b.…”
Section: Synthesis Synthesis Of 4-(2-hydroxyethoxy)-2-methoxybenzalde...mentioning
confidence: 99%
“…In recent years, the design and synthesis of bio-based hard monomers have been exploited to develop high performance polymeric materials for replacement of engineering plastics. Some bio-based hard monomers were used to obtain polymers with high glass transition temperatures, such as spirofuran-based monomers ( Figure 10 ) [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. It is also found that the CO 2 emission for production of the bio-based rigid monomer 1 ( Figure 10 a,b) was much lower than that of fossil-based monomers, which gave rise to high performance polymers with a degradation temperature of up to 300 °C based on thermal gravimetric analysis (TGA) ( Figure 10 c) [ 86 ].…”
Section: Conclusion and Future Prospects Of Bio-based Polymersmentioning
confidence: 99%